The clonal relation of primary upper urinary tract urothelial carcinoma and paired urothelial carcinoma of the bladder. Issue 4 (13th October 2020) - van Doeveren, Thomas; Nakauma‐Gonzalez, Jose A.; Mason, Andrew S.; van Leenders, Geert J. L. H.; Zuiverloon, Tahlita C. M.; Zwarthoff, Ellen C.; Meijssen, Isabelle C.; van der Made, Angelique C.; van der Heijden, Antoine G.; Hendricksen, Kees; van Rhijn, Bas W. G.; Voskuilen, Charlotte S.; et al.
Abstract: The risk of developing urothelial carcinoma of the bladder (UCB) in patients treated by radical nephroureterectomy (RNU) for an upper urinary tract urothelial carcinoma (UTUC) is 22% to 47% in the 2 years after surgery. Subject of debate remains whether UTUC and the subsequent UCB are clonally related or represent separate origins. To investigate the clonal relationship between both entities, we performed targeted DNA sequencing of a panel of 41 genes on matched normal and tumor tissue of 15 primary UTUC patients treated by RNU who later developed 19 UCBs. Based on the detected tumor‐specific DNA aberrations, the paired UTUC and UCB(s) of 11 patients (73.3%) showed a clonal relation, whereas in four patients the molecular results did not indicate a clear clonal relationship. Our results support the hypothesis that UCBs following a primary surgically resected UTUC are predominantly clonally derived recurrences and not separate entities. Abstract : What's new? Patients treated by radical nephroureterectomy for upper urinary tract cancer have an increased risk of developing bladder carcinoma following surgery. It remains unclear, however, whether the upper urinary tract cancer and subsequent bladder carcinoma are clonally related or have separate origins. This targeted DNA sequencing study shows that almost 75% of patients have tumors that are clonally related, suggesting that seeding of tumor cells is the main mechanism of bladder carcinoma development following radical nephroureterectomy. This result underscores the need to minimalize the risk of seeding during surgery and/or diagnostic ureterorenoscopy plus biopsy, and to apply peri‐operative intravesical instillations with chemotherapy.